The Table Text Jagadbhūṣaṇa of Haridatta: The First Chapter on the Sun and the Moon - Melnad, Keshav; Montelle, Clemency; K., Ramasubramanian (History of Science in South Asia)

(untitled) (University of Alberta Library, 2024)
In the seventeenth century, the astronomer Haridatta of Mewar, Rājasthān, produced a table text named the Jagadbhūṣaṇa (epoch Śaka 1560, or 1638 CE). This table text provided calendar makers with a complete set of data and associated procedures for the computation of the annual calendar known in Sanskrit as a pañcāṅga. The tables are huge and represent an enormous computational effort, and the astronomical structure that underlies them is somewhat akin to the Babylonian Goal Year texts and similar cyclic schemes set out by Ptolemy and al-Zarqālī. The accompanying text consists of around one hundred and thirty verses organised into five chapters. This article is the first in a series that presents the Sanskrit text of the Jagadbhūṣaṇa along with a translation and a detailed technical commentary of the text and analysis of the associated tabular material, chapter by chapter. In the opening chapter, Haridatta begins the work with a lengthy encomium to his patron, Mewar Rajput Jagatsiṃha, before describing the procedures by which the true longitudes and motions of the sun and the moon can be determined using the accompanying tabulated data.